Mukhtashar shahih Bukhari Muhammad Nashiruddin Al-Albani ; penerjemah, Asep Saefullahm Kamaluddin Saadiyatulharamain ; editor, Abu Rania, Abu Fahmi, Fajar Inayati - Al-Albani, Muhammad Nashiruddin (Pustaka Azzam, 2007)
532 hlm. 23 cm.